2018
DOI: 10.3390/ijerph15102126
|View full text |Cite
|
Sign up to set email alerts
|

Associations between Adherence to the Mediterranean Diet and Lifestyle Assessed with the MEDLIFE Index among the Working Population

Abstract: The adherence to the Mediterranean diet is beneficial for cardiovascular diseases prevention. The study aim is to use Mediterranean lifestyle (MEDLIFE) questionnaire for estimation of Mediterranean lifestyle habits among the working population and to establish MEDLIFE score correlation with the risk factors for cardiovascular diseases. In the study has participated 366 workers from Croatia, which fulfilled MEDLIFE and validated food frequency questionnaire (FFQ) questionnaire. The multivariate logistic regress… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
11
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 23 publications
8
11
1
Order By: Relevance
“…At the study baseline, the average energy intake of the participants in both groups was higher than recommended for their gender, age, and level of physical activity as a result of higher consumption of animal-origin foods and their products, industrially processed cereals, sweets, sweetened beverages, and added fats than recommended, which is in line with Croatian studies on diet quality [ 27 , 47 , 48 , 49 , 50 , 51 ]. Increased consumption of the above-mentioned food is significantly associated with weight gain, obesity, obesity-related complications, and low-grade chronic inflammation [ 10 , 12 ].…”
Section: Discussionsupporting
confidence: 83%
“…At the study baseline, the average energy intake of the participants in both groups was higher than recommended for their gender, age, and level of physical activity as a result of higher consumption of animal-origin foods and their products, industrially processed cereals, sweets, sweetened beverages, and added fats than recommended, which is in line with Croatian studies on diet quality [ 27 , 47 , 48 , 49 , 50 , 51 ]. Increased consumption of the above-mentioned food is significantly associated with weight gain, obesity, obesity-related complications, and low-grade chronic inflammation [ 10 , 12 ].…”
Section: Discussionsupporting
confidence: 83%
“…In addition, 61.64% of the workers in our study consumed legumes once or twice per week, while the frequency of consumption was lower for meat (23.49%). Although the Mediterranean dietary pattern is also dominant in countries such as Croatia and Portugal [45,46], a study carried out in workers from Croatia [47] showed higher bread consumption (91%) and lower consumption of fruit (51.20%) and vegetables (33.60%) than in our study. In Portugal, the frequency of consumption of fruit and vegetables was found to be higher (53% and 76%, respectively), but it was lower for milk (74.60%) and meat (17%) compared with the results of our study [48].…”
Section: Discussioncontrasting
confidence: 74%
“…In particular, a significant difference in the MD score emerged between women with a high school degree (6.85 ± 1.41) and women with an academic degree (7.32 ± 1.80). These results are comparable to others in the literature (Pavičić Žeželj et al., 2018). As reported by Cano‐Ibáñez N. et al in their cross‐sectional study on subjects with metabolic syndrome, educational level was a variable that significantly influenced a better micronutrient density, as the dietary behavior is healthier in people with a higher educational background and higher socioeconomic status (Cano‐Ibáñez et al., 2019).…”
Section: Discussionsupporting
confidence: 91%